Interferential electrical stimulation improves peripheral vasodilatation in healthy individuals - Santos, Francisco V. (2013)
BACKGROUND: Interferential electrical stimulation (IES), which may be linked to greater penetration of deep tissue, may restore blood flow by sympathetic nervous modulation; however, studies have found no association between the frequency and duration of the application and blood flow. We hypothesized that 30 min of IES applied to the ganglion stellate region might improve blood flow redistribution.OBJECTIVES: The purpose of this study was to determine the effect of IES on metaboreflex activation in healthy individuals.METHOD: Interferential electrical stimulation or a placebo stimulus (same protocol without electrical output) was applied to the stellate ganglion region in eleven healthy subjects (age 25±1.3 years) prior to exercise. Mean blood pressure (MBP), heart rate (HR), calf blood flow (CBF) and calf vascular resistance (CVR) were measured throughout exercise protocols (submaximal static handgrip exercise) and with recovery periods with or without postexercise circulatory occlusion (PECO+ and PECO -, respectively). Muscle metaboreflex control of calf vascular resistance was estimated by subtracting the area under the curve when circulation was occluded from the area under the curve from the AUC without circulatory occlusion.RESULTS:At peak exercise, increases in mean blood pressure were attenuated by IES (p<0.05), and the effect persisted under both the PECO+ and PECO- treatments. IES promoted higher CBF and lower CVR during exercise and recovery. Likewise, IES induced a reduction in the estimated muscle metaboreflex control (placebo, 21±5 units vs.IES, 6±3, p<0.01).CONCLUSION: Acute application of IES prior to exercise attenuates the increase in blood pressure and vasoconstriction during exercise and metaboreflex activation in healthy subjects.